La agenda de competitividad y los retos para el aprovechamiento de la política comercial en Colombia (2015)
Competitiveness is an indisputable reference instrument for the intentionality, but also the operation, policies and actions of a country, to improve its references of good practices. This if the international standards are met, which not only facilitate to entry into new markets, but also to identify new opportunities, and to diversify business initiatives.